Model Kepemimpinan Situasional dan Transformasional Kepala Sekolah SMAK Yos Sudarso Batu - Dismas Kwirinus; Archadius Mbabho Jando; Gregorius Avi; Melki Nino; Yulianus Hironi Ndua (Universitas Muhammadiyah Makassar, 2023)
The focus of this study is to explain the situational and transformational leadership models that exist in the Principal of SMAK Yos Sudarso Batu. The leadership models that can be observed from this school principal are situational leadership and transformational leadership. These two terms are quite foreign to the ears, because they are rarely mentioned in an organization or institution that are encountered on a daily basis. This leadership model is an expression of how Principal Yos Sudarso is in the organization or foundation he leads. This study aims to describe and analyze the basis, character, and pattern of situational and transformational leadership of school principals. The researcher uses descriptive qualitative method which produces data in the form of words and in writing or verbally from the people and observed behavior. The findings of this study are that a leader who lives a situational and transformational leadership model is a leader who is able to set clear, specific and measurable organizational goals. Cooperative, capable and militant leader. This leader also has a strong determination and commitment, is able to create synergies within the organization and is able to mobilize all member resources.